2017
DOI: 10.1007/s40243-017-0091-7
|View full text |Cite
|
Sign up to set email alerts
|

Review: on rare-earth perovskite-type negative electrodes in nickel–hydride (Ni/H) secondary batteries

Abstract: Rare-earth perovskites-type oxides are compounds with the general formula ABO 3 . There are many industrial and research applications related to their properties such as photocatalytic activity, magnetism, or pyroferro and piezo-electricity, and interest in these compounds in the field of energy storage and conversion is growing. Rare-earth perovskite-type oxides may be used in nickelmetal hydride (Ni/MH) battery technology because these materials may store hydrogen in strong alkaline environments, and also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 85 publications
0
18
0
Order By: Relevance
“…1b) revealed that La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3 particles displayed an irregular morphology and were agglomerated with each other. Considering the application, it is always an advantage to use of ultrafine oxides over bulk ones, since the diffusion path of both hydrogen ions and electrons can be shortened using ultrafine particles as demonstrated in previous studies [13,16].…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…1b) revealed that La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3 particles displayed an irregular morphology and were agglomerated with each other. Considering the application, it is always an advantage to use of ultrafine oxides over bulk ones, since the diffusion path of both hydrogen ions and electrons can be shortened using ultrafine particles as demonstrated in previous studies [13,16].…”
Section: Resultsmentioning
confidence: 90%
“…Interestingly, the obvious expansion of the cell volume in the perovskite-type electrodes is small in comparison to the volumetric expansion experienced by traditional intermetallic alloys (up to 25% volume change) [20]. The change in the cell volume is attributed to the nature of the hydrogen uptake in perovskites [13]. Unlike conventional metal hydride alloys, in a perovskite, the dissociated H 2 O molecule, specifically H ?…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations